2011
DOI: 10.1089/neu.2010.1476
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Endothelial Nitric Oxide Gene and Cerebral Blood Flow after Severe Traumatic Brain Injury

Abstract: Experimental studies suggest that nitric oxide produced by endothelial nitric oxide synthase (NOS3) plays a role in maintaining cerebral blood flow (CBF) after traumatic brain injury (TBI). The purpose of this study was to determine if common variants of the NOS3 gene contribute to hypoperfusion after severe TBI. Fifty-one patients with severe TBI were studied. Cerebral hemodynamics, including global CBF by the stable xenon computed tomography (CT) technique, internal carotid artery flow volume (ICA-FVol), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
1
38
0
1
Order By: Relevance
“…Genetic variants of eNOS influence the maintenance of CBF after severe TBI. As in SAH, patients with decreased endogenous eNOS levels had poorer outcomes than patients with alleles that did not affect eNOS levels (Robertson et al, 2011).…”
Section: Enos Functionmentioning
confidence: 93%
“…Genetic variants of eNOS influence the maintenance of CBF after severe TBI. As in SAH, patients with decreased endogenous eNOS levels had poorer outcomes than patients with alleles that did not affect eNOS levels (Robertson et al, 2011).…”
Section: Enos Functionmentioning
confidence: 93%
“…[133][134][135] Inflammation increases excitability of blood vessels, 136 neurons, [137][138][139] and glia 140 that may induce cortical spreading depression. [133][134][135] Inflammation increases excitability of blood vessels, 136 neurons, [137][138][139] and glia 140 that may induce cortical spreading depression.…”
Section: Box 7-how Traumatic Brain Injury (Tbi) Can Trigger Post-tramentioning
confidence: 99%
“…131 More severe TBI can disrupt the blood-brain barrier leading to extrusion of neutrophils from leaky blood vessels contributing to an inflammatory cascade. [133][134][135] Inflammatory mediators induced by brain injury may alter the function and excitability of meningeal and cerebrovascular structures, 136 neurons, [137][138][139] and glia 140 possibly leading to cortical spreading depression (CSD). 132 Microglia plays an important role in brain response to TBI.…”
Section: Box 7-how Traumatic Brain Injury (Tbi) Can Trigger Post-tramentioning
confidence: 99%
See 1 more Smart Citation
“…CBF is affected by functional variants in the gene for nitric oxide synthase [63], and individuals with such polymorphisms may have a decreased ability to maintain adequate CBF following TBI [64]. Using PET, it has recently been found that the BDNF Val66Met polymorphism increased resting CBF in the prefrontal cortex and hippocampus [65 & ].…”
Section: Other Factors That Influence Plasticity and Recoverymentioning
confidence: 99%